SERVICE DISTRIBUTION AND SATISFACTION TOWARD CUSTOMER LOYALTY - R. Agoes Kamaroellah; Anis Eliyana; Reza Mubarak (Univeristas Islam Bandung, 2021)
Automated Teller Machines (ATMs) are a medium for financial transactions. This study investigates the impact of service distribution and service satisfaction on customer loyalty on ATM usage of the BRI Syariah Sub-Branch Office (KCP) Pamekasan. Data obtained from primary data in ATM user respondents' Form, the data analyzed by SEM with PLS approach. The calculation is carried out in two phases, the first-order phase, and the second-order phase. A validity and reliability test revealed that all three variables were valid and reliable in the first-order phase. At the same time, the second-order phase was used, CFA, and Construct Reliability. Subsequently, an Inner Model test uncovered that the Service Distribution has no significant effect on Customer Loyalty. Contrastively, Service Satisfaction has a significant positive impact on customer loyalty. The goodness of Fit based on R-Square reveals that Service Distribution and Service Satisfaction can explain Service Loyalty at BRI Syariah KCP Pamekasan ATM very well.